Laser cladding of a cobalt-based superalloy on austenitic stainless steel Deposição a laser de superliga à base de cobalto sobre aço inoxidável austenítico - Veiga M.T.* (2021)
© 2021, University Federal de Uberlandia. All rights reserved.The present work aimed to determine laser processing parameters for deposition of defect-free Stellite 6 coatings and with suitable geometry on austenitic stainless steel. Coatings were deposited with a diode laser source, equipped with a continuous coaxial head, using different beam powers and scanning speeds. The geometry (width, height, undulation and dilution) of the coatings was measured by analyzing the cross section. These obtained data were used to model the process (response surface) and to estimate optimized parameters (function desirability), which were later verified experimentally. The microstructure of the coatings deposited with the optimized parameters was characterized by optical and scanning electron microscopy. The proper selection of parameters resulted in coatings with good surface finish, free of superficial defects and low dilution. The results show that the laser power had a significant effect on the dilution, while the speed influenced the height of the deposited layer. The microstructure resulting from the coating is composed of dendrites rich in cobalt and interdendritic region with chromium carbides. The hardness results are in line with the predicted in the literature.